2003
DOI: 10.1089/107999003322558782
|View full text |Cite
|
Sign up to set email alerts
|

Fever After Zoledronic Acid Administration Is Due to Increase in TNF-αand IL-6

Abstract: The most common adverse event typically associated with bisphosphonate therapy is transient fever. The aim of this study was to define the role of the main cytokines of the acute-phase reaction interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) involved in the pathogenesis of zoledronic acid-induced fever. Eighteen consecutive cancer patients with bone metastases were treated, for the first time, with a single dose of 4 mg zoledronic acid infusion. They were prospectively evaluated for circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 25 publications
8
75
2
2
Order By: Relevance
“…In our result, as documented also by other investigators we observed a sharp and statistically significant increase in IL-6 and TNF-α median values on days 1 and 2 after zoledronic acid infusion [19,20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our result, as documented also by other investigators we observed a sharp and statistically significant increase in IL-6 and TNF-α median values on days 1 and 2 after zoledronic acid infusion [19,20].…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, we described the modification in serum level of important cytokine in MM. About the anti-angiogenic effect recently demonstrated in vivo although the lack of long-lasting reduction of VEGF and PDGF that we noticed differently from what happen in solid cancer [10,20], we could not exclude that zoledronic acid express its anti-myeloma activity by inhibiting VEGF (reduced after day 7) and PDGF, even though zoledronic acid may not have an effect on the cytokine themselves. It is possible that this drug may have an impact on the effect of VEGF and PDGF on signalling that leads to blood vessel development or it also may have an impact on the effect of VEGF and PDGF on myeloma cells directly like hypothesized in some recent study, previously mentioned.…”
Section: Discussioncontrasting
confidence: 71%
“…The exact mechanism underlying these reactions is unclear. However, it is thought to result from the activation of γδT cells which may lead to an increased circulating levels of interleukin-6 and tumor necrosis factor-α (10) . These reactions were the only ones by the patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Often time, they were informed about the possible adverse effects and advised to contact the doctor in case of an emergency. Post-infusion adverse effects are common after zoledronic acid infusion and are thought to result from increased levels of inflammatory mediators in circulation as a response to infusion (10) . Therefore, we prescribed oral ibuprofen 800 mg/day for three daysto prevent post-infusion adverse effects that are induced by inflammatory mediators.…”
Section: Patients and Outcome Measuresmentioning
confidence: 99%
“…nearly 3 mg/dL at 21 days after infusion of 4 mg of zoledronic acid. 12 Key point: All patients who are to begin receiving either oral or IV bisphosphonate therapy should have adequate calcium and vitamin D intake. If any concerns about nutritional status or absorptive capacity arise, serum levels of 25-hydroxyvitamin D, calcium phosphorus, and parathyroid hormone as well as urinary calcium excretion should be assessed and abnormalities addressed before initiating bisphosphonate therapy.…”
Section: Hypocalcemiamentioning
confidence: 99%